Implementation of problem based learning with cmaptools media to increase problem solving abilities - Desy Eka Muliani (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2021)
This study aims to analyze the comparison of increasing the problem solving ability between groups of students who get problem-based learning with cmaptools media, and groups of students who get conventional learning. The research method used was a quasi experiment with the Randomized Control Group Pretest-Posttest design and descriptive method. The instruments used include: problem solving ability test. The improvement of problem solving ability is determined through the average N-gain. The results of the calculation of the average N-gain obtained that the average N-gain group of students who get problem-based learning with cmaptools is 0.78 (high category), while the average N-gain group of students who get conventional learning is 0.68 (medium category). The results of statistical tests (t-test) show that problem-based learning with cmaptools can further improve problem-solving abilities compared to conventional learning.